SPLMax: Exploiting the Simple Path Introduced Locality for Maximum Flow Acceleration - Wei, Wei; Liu, Yang; Zhang, Ruqing (IEEE communications letters, 2018)
As a basic problem in graph theory, the maximum flow (max-flow) problem has important applications in networking and communication related areas. The simple path introduced locality is implicit in classic max-flow algorithms, i.e., only the vertices in simple paths between source and sink are involved in max-flow calculation. However, this kind of locality is completely ignored in existing acceleration methods, which leads to a lot of useless calculations and seriously degrades the acceleration effect. We propose simple-path locality based max-flow acceleration algorithm (SPLMax) to address the problem, where an overlay graph is built and used to accelerate calculation by only including necessary vertices. Random graph based simulations show that with SPLMax, at best only 0.001% vertices (i.e., 1/71193) in the graph need to be involved in max-flow calculation. For the comparison using real-world graphs, SPLMax has the minimal pre-processing time (at most 109 times faster than other methods) and minimal average max-flow computation time (at most 4.3 times faster than other methods).